Mindfulness-Based Program Embedded Within the Existing Curriculum Improves Executive Functioning and Behavior in Young Children: A Waitlist Controlled Trial - Janz, Philip; Dawe, Sharon; Wyllie, Melissa (Frontiers in Psychology, 2019)
There is a growing evidence base for mindfulness-based interventions in educational settings. Notably, there has been little investigation of the potential benefits of classroom-based mindfulness programs in very young children, despite early childhood being a period characterized by the development of self-regulation and executive functions. The present study investigated the effects of a mindfulness-program that was embedded within a school curriculum. This waitlist controlled trial investigated the effects of a mindfulness program, CalmSpace, delivered by classroom teachers across two school terms. A total of 55 students, Mage = 76.4 months, SD = 8.62, were allocated to participate in CalmSpace in Terms 3 and 4. Thirty-six students in the waitlist control condition, Mage=80.53 months, SD=13.04, participated in the intervention in Term 4. Direct measures of executive functioning and teachers’ report of children’s behavior were obtained at the beginning and end of Term 3, and at the end of Term 4. Children who received the CalmSpace program displayed increased executive function skills on measures of cognitive flexibility and improved teacher reported behavior when compared to the waitlist control group. A trend (p=.069) was found for reaction time but no effects on accuracy for a measure of behavioral inhibition. Notably, waitlist control students improved favorably once they received the CalmSpace program. The findings demonstrate that implementing the CalmSpace program can lead to improvements in EF and attention for young children. Despite limitations, this study provides promising evidence that the inclusion of focused, targeted mindfulness activities throughout the day may represent a value-added component to the regular school curriculum that can result in benefits for the students.